Sedimentary response to Milankovitch-type climatic oscillations and formation of sediment undulations: evidence from a shallow-shelf setting at Gela Basin on the Sicilian continental margin. (15th January 2015) - Kuhlmann, Jannis; Asioli, Alessandra; Trincardi, Fabio; Klügel, Andreas; Huhn, Katrin
Abstract: A multi-proxy chronological framework along with sequence-stratigraphic interpretations unveils composite Milankovitch cyclicity in the sedimentary records of the Last Glacial–Interglacial cycle at NE Gela Basin on the Sicilian continental margin. Chronostratigraphic data (including foraminifera-based eco-biostratigraphy and δ 18 O records, tephrochronological markers and 14 C AMS radiometric datings) was derived from the shallow-shelf drill sites GeoB14403 (54.6 m recovery) and GeoB14414 (27.5 m), collected with both gravity and drilled MeBo cores in 193 m and 146 m water depth, respectively. The recovered intervals record Marine Isotope Stages and Substages (MIS) from MIS 5 to MIS 1, thus comprising major stratigraphic parts of the progradational deposits that form the last 100-ka depositional sequence. Calibration of shelf sedimentary units with borehole stratigraphies indicates the impact of higher-frequency (20-ka) sea level cycles punctuating this 100-ka cycle. This becomes most evident in the alternation of thick interstadial highstand (HST) wedges and thinner glacial forced-regression (FSST) units mirroring seaward shifts in coastal progradation. Albeit their relatively short-lived depositional phase, these subordinate HST units form the bulk of the 100-ka depositional sequence. Two mechanisms are proposed that likely account for enhanced sediment accumulation ratios (SAR) of up to 200 cm/ka during these intervals: (1) intensified activity of deep and intermediate Levantine Intermediate Water (LIW) associated to the drowning of Mediterranean shelves, and (2) amplified sediment flux along the flooded shelf in response to hyperpycnal plumes that generate through extreme precipitation events during overall arid conditions. Equally, the latter mechanism is thought to be at the origin of undulated features resolved in the acoustic records of MIS 5 Interstadials, which bear a striking resemblance to modern equivalents forming on late-Holocene prodeltas of other Mediterranean shallow-shelf settings. Highlights: A multi-proxy chronological framework from drilled cores at Gela Basin is proposed. Depositional architecture is paced by Milankovitch-type cyclicity (100-ka/20-ka). The bulk of sedimentation corresponds to interstadial HST deposits during MIS5. Sediment dispersal appears to be strongly dependent on paleoclimatic changes in LIW. Genesis of intra-MIS5 sediment undulations relates to hyperpycnal river floods.